Transformation Of Moral Values And Manners Of Early Childhood In Today's Educational Context - Nuswantari, Rahajeng Silmi; Cholimah, Nur (LPPM Universitas PGRI Sumatera Barat, 2024)
Transformation education child age early childhood education (PAUD) based moral values and manners has become must in face dynamics social and development technology that has an impact on the formation character and morality children. In the digital era, children the more exposed to values that conflict with norms and culture sublime, such as individualism and consumerism, which have the potential weaken mark empathy, responsibility answer, and polite polite. Research This aiming For analyze How PAUD institutions respond challenge the through approach education adaptive and contextual characters. The methods used is studies qualitative with approach study literature from various source scientific latest. Study results show that formation morality in children age early will effective If moral values are integrated in a way explicit in curriculum, supported by the example of teachers, as well as close collaboration between school, family and environment society. Transformation Early childhood education must nature holistic and collaborative For realize generation character in the middle current globalization